1998
DOI: 10.1159/000040890
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α-Thalassemia on Cholelithiasis in SS Patients with Elevated Hb F

Abstract: Chronic hemolysis, with consequent hyperbilirubinemia, predisposes SS patients to pigment gallstones. The other factors which influence the development of stones in these patients have not been identified. We have carried out a combined prospective and retrospective study of SS patients in Kuwait and specifically investigated the influence of coexistent α-thal trait on the prevalence of gallstones. A total of 45 patients (30 males, 15 females) with ages ranging from 1 to 16 years (mean 7.2 ± 3.1) were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
(18 reference statements)
0
14
3
Order By: Relevance
“…Unlike in SCA patients bearing the Arab-Indian b S haplotype [7] the protective effect of a-thalassemia for cholelithiasis is not observed in our SCA patients predominantly of Benin b S haplotype. Such a discrepancy between these SCA population groups could be related to significant reduction in hemolysis associated with higher mean HbF levels associated with the Arab-Indian b S haplotype and/or to much higher frequency of a-thalassemia than in our study population [9,10].…”
contrasting
confidence: 94%
See 1 more Smart Citation
“…Unlike in SCA patients bearing the Arab-Indian b S haplotype [7] the protective effect of a-thalassemia for cholelithiasis is not observed in our SCA patients predominantly of Benin b S haplotype. Such a discrepancy between these SCA population groups could be related to significant reduction in hemolysis associated with higher mean HbF levels associated with the Arab-Indian b S haplotype and/or to much higher frequency of a-thalassemia than in our study population [9,10].…”
contrasting
confidence: 94%
“…The promoter region of UGT1A1 gene contains a run of variable number of thymine-adenine repeats, (TA) n (n ¼ 5 to 8) with an inverse relationship between the size of this microsatellite and the promoter activity. We have previously shown that SCA patients fell into three risk groups according to their UGT1A1 genotype: group 1 [homozygous (TA) 6 /(TA) 6 and heterozygous with at least one (TA) 5 allele], group 2 [heterozygous (TA) 6 /(TA) 7 and (TA) 6 /(TA) 8 ], and group 3 [homozygous (TA) 7 /(TA) 7 and heterozygous (TA) 7 /(TA) 8 ], associated respectively with low, intermediate, and high mean unconjugated bilirubin levels and risk of cholelithiasis [4]. a-Thalassemia, frequently encountered in patients with SCA, is known to diminish the degree of hemolytic anemia [5,6] and has been associated with a lower occurrence of cholelithiasis in SCA patients bearing the Arab-Indian b S haplotype [7].…”
mentioning
confidence: 99%
“…It is known that the coinheritance of a-thalassaemia and SCD determinants reduces the mean corpuscular haemoglobin concentration of red blood cells, which tends to inhibit sickling. It was observed that the coexistence of athalassaemia decreases the chance of developing gallstones in Arab Indian haplotype SCD patients, which may be related to lower haemolysis, as suggested by their predisposition to present, in general, higher mean Hb levels (Haider et al 1998). In addition, Adekile et al (2005) observed that the b-globin haplotype and the coexisting athalassaemia did not have significant influence on serum bilirubin levels in Arab Indian haplotype SCD patients (Adekile et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This protects them from many of the complications of the disease. In particular, they retain their splenic function and are less prone to severe bacterial infections [5, 6, 7, 8]. Brain infarcts, leg ulcers and hand-and-foot syndrome are all rare.…”
Section: Introductionmentioning
confidence: 99%